2017
DOI: 10.1093/femsre/fux006
|View full text |Cite
|
Sign up to set email alerts
|

Toxin–antitoxin systems and their role in disseminating and maintaining antimicrobial resistance

Abstract: Toxin–antitoxin systems (TAs) are ubiquitous among bacteria and play a crucial role in the dissemination and evolution of antibiotic resistance, such as maintaining multi-resistant plasmids and inducing persistence formation. Generally, activities of the toxins are neutralised by their conjugate antitoxins. In contrast, antitoxins are more liable to degrade under specific conditions such as stress, and free active toxins interfere with essential cellular processes including replication, translation and cell-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 102 publications
0
81
0
Order By: Relevance
“…The multiresistant 28Eco12 isolate harbored only the phage-like IncY plasmid p28Eco12, which is genetically related to the plasmids p266917_2_02 (88% coverage, 99% identity, GenBank accession number CP026725.1), p1303_95 (91% coverage, 99% identity, GenBank accession number CP009168.1), p1 of Salmonella enterica strain ty3-243 (90% coverage, 93% identity, GenBank accession number LT905089.1), and the bla KPC -containing pCRKP-59-KPC (89% coverage, 94% identity, GenBank accession number KX928752.1). Although this plasmid does not transport resistance genes, it appears to be conserved in almost all bla OXA-244 -containing E. coli strains included in our analysis, and its permanence is perhaps caused by the presence of the P1 phd-doc toxin-antitoxin system that participates in host post-segregational killing [12]. Currently, there is limited knowledge about this phage-like IncY-plasmid family (for instance, the 37% of their ORFs is encoding for hypothetical proteins), but it is also becoming a genetic platform to transport important resistance genes, such as bla CTX-M-15 and mcr-1; the latter confers resistance to colistin [13].…”
Section: Discussionmentioning
confidence: 97%
“…The multiresistant 28Eco12 isolate harbored only the phage-like IncY plasmid p28Eco12, which is genetically related to the plasmids p266917_2_02 (88% coverage, 99% identity, GenBank accession number CP026725.1), p1303_95 (91% coverage, 99% identity, GenBank accession number CP009168.1), p1 of Salmonella enterica strain ty3-243 (90% coverage, 93% identity, GenBank accession number LT905089.1), and the bla KPC -containing pCRKP-59-KPC (89% coverage, 94% identity, GenBank accession number KX928752.1). Although this plasmid does not transport resistance genes, it appears to be conserved in almost all bla OXA-244 -containing E. coli strains included in our analysis, and its permanence is perhaps caused by the presence of the P1 phd-doc toxin-antitoxin system that participates in host post-segregational killing [12]. Currently, there is limited knowledge about this phage-like IncY-plasmid family (for instance, the 37% of their ORFs is encoding for hypothetical proteins), but it is also becoming a genetic platform to transport important resistance genes, such as bla CTX-M-15 and mcr-1; the latter confers resistance to colistin [13].…”
Section: Discussionmentioning
confidence: 97%
“…According to studies, six different classes of TA systems have been identified among which type II systems is known to have a role in persister cells formation. In type II TA systems, protein antitoxin has two domains; one domain binds a palindromic sequence of the promoter leading to the repression of type II TA operon, while the second domain binds the cognate toxin leading to its inhibition (17). In the stress condition, unstable antitoxin is degraded by proteases such as ClpXP and ClpAP, hence the free toxin can affect major cellular processes leading to bacterial persistence and dormancy (27).…”
Section: Discussionmentioning
confidence: 99%
“…In the stress condition, the labile antitoxin is selectively degraded by cellular proteases such as Lon and clpXP. Destruction of antitoxins makes toxin to target the essential bacterial processes (protein translation, and cell-wall synthesis, DNA replication) and triggers various functions such as switching of bacteria into dormant, stress management, bacterial persistence (17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…TA loci usually are comprised of two genes, which encode a stable toxin and an unstable antitoxin that inhibits the toxin. TAs are currently divided into six distinct classes on the basis of the proteomic nature of the corresponding antitoxin (1,16). See Fig.…”
Section: Toxin-antitoxin Systemsmentioning
confidence: 99%
“…Antimicrobial resistance is one of the main problems of the 21st century. The rapid spread of multidrug-resistant (MDR) pathogens has been described as a global crisis that may lead to an era without effective antibiotics (1). Failure of antibiotic treatment is typically attributed to resistance.…”
Section: Introductionmentioning
confidence: 99%